A construção discursiva em arquivística: uma análise do percurso histórico e conceitual da disciplina por meio dos conceitos de classificação e descrição - Barros, Thiago Henrique Bragato [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Discourse Analysis is a discipline that has theoretical and methodological characteristics that may contribute to the theory growth of the Archival Science. The study of discourse helps to understand how its construct certain linguistic formations, concerned mainly with the context in which the text was produced. As the Archival Science a product of historically constructed knowledge, the conceptual context of production ultimately reflected in different streams of thought and approach. Thus contributes to the discourse analysis and Archival Science, since it has a theoretical approach in this regard relating the discourse produced by Archival Science manuals . We discussed the basic concepts of archival organization: Description and Organization divided into two complementary phases Classification and Arrangement. These concepts were discussed by means of its historical and conceptual in a series of works. We analyzed a total of six manuals / books, divided into before and after the development of the assumptions of Appraisal. They are: The Manual for the Arrangement and Description of Archives, (Handleiding voor het ordenen em beschreijven van Archieven) by Muller, Feith, and Fruin (Ed.1 1898) the A manual of archive administration including the problems of war archives and archive making (1st Ed 1922) by Sir Hillary Jenkinson, responsible for the first utterances of the archival techniques and the manual that still responsible for modifying a number of practices in the archives, the Modern Archives: Principles and Techniques (1st Ed 1956) Theodore R. Schellenberg. And of all the most current manuals, were selected to Antonia Heredia Herrera, Archivística General (1 Ed. 1986) and Arquivos Permanetes de Heloisa Liberalli Bellotto (1 Ed.1990). As a counterpoint, and thus not excluding what was thought previously presented by the textbooks, but with different ways of perceiving the same ...(Complete abstract click electronic address below)
Keywords: Arquivologia; Linguística; Análise do discurso; Classificação - Arquivos; Discourse Analysis; Archival science; Classification; Arragement; Description